Challenges, opportunities, and a research roadmap for downwind wind turbines. Issue 2 (18th September 2021) - Bortolotti, Pietro; Ivanov, Hristo; Johnson, Nick; Barter, Garrett E.; Veers, Paul; Namura, Nobuo
Abstract: This study investigates the challenges and opportunities presented by downwind wind turbines and offers a roadmap of future research pathways to maximize their potential. Multidisciplinary design, analysis, and optimization comparison studies between upwind and downwind configurations on a modern 10‐MW offshore wind turbine are presented to support the discussion. On one hand, the downwind rotor is found to consistently have a smaller swept area under loading. As a result, the downwind design produces less annual energy production (−1.2%). On the other hand, lighter blades for the downwind configuration lead to lower capital costs (−1.7%), so there is little difference in the levelized cost of energy between the two. Key ultimate and fatigue loads are compared, with some values increasing in the downwind configuration, while others decrease. The impact of a downwind configuration on the tower and the impacts of cone and tilt angles and free‐yaw system on the levelized cost of energy are also investigated. The results show a mix of some advantages and disadvantages. Given these results, four areas of research in advanced controls, highly tilted rotors, higher fidelity aerodynamic models, and floating wind are proposed for downwind wind turbines.